The genome sequence of the broad-bordered yellow underwing, Noctua fimbriata (Schreber, 1759) - Holland, PWH (F1000 Research Ltd, 2021)
We present a genome assembly from an individual female Noctua fimbriata (the broad-bordered yellow underwing; Arthropoda; Insecta; Lepidoptera; Noctuidae). The genome sequence is 574 megabases in span. The complete assembly is scaffolded into 32 chromosomal pseudomolecules, with the W and Z sex chromosomes assembled.